To Explore the Influence of College Students’ Emotional Reseponse on Visual Art Intangible Cultural Heritage on their Participation in Tianjin, China - Wang, Shan; Ghazali, Rusmawati; Jiao, Jieqiong_; Wardi , Rainal Hidayat (Journal of Ecohumanism, 2024)
Objective To explore the impact of students’ emotional responses to visual arts intangible cultural heritage on their participation in Tianjin, China, and explore effective strategies to enhance students’ emotional responses and classroom participation. Methods A total of 164 students majoring in art in a school in Tianjin were selected by random sampling method, and questionnaires on class participation and emotional response were used to conduct a survey. Statistical analysis was carried out by descriptive statistics, independent sample T-test, correlation analysis and other methods. Results The class participation of art majors was at the upper middle level (M = 3.77, with the highest score of behavior participation being 3.99), and the emotional response was also at the upper middle level (M = 3.87, with the highest score of behavior being 3.98). There was a significant correlation between emotional response and class participation in all dimensions and total scores (r = 0.670, P < 0.01). The regression analysis shows that the prediction of emotional response to class participation is 49.20%. Conclusion Improving students’ emotional response can effectively improve students’ participation in class.